Penetapan Alokasi Sawah Penerima Air Irigasi Berdasarkan Kondisi Hidroklimatologi di Daerah Irigasi Cihea - Latief Mahir Rachman; Dwi Putro Tejo Baskoro; Nur Etika Karyati (Jurnal Ilmu Pertanian Indonesia, 2022)
One of the main supporting factors for the agricultural sector in the Cihea Irrigation Area is the availability of sufficient water resources. However, uncertain climatic conditions due to climate change lead the changes in the rain distribution and affect the availability of water resources. The study aims to (1) assess the land water balance and drought index in Cihea Irrigation Area and (2) develop alternatives related to irrigation priority locations based on hydro climatological conditions. The water balance was analyzed using the Thornthwaite-Mather method (1957), while the irrigation priority locations were determined using the composite performance index method. Based on the annual water balance analysis, this irrigation area had a 568 mm/year water surplus. However, there was a water shortage from July to October, at 132 mm per month. From ten land systems,the highest deficit was in SL_9, while the lowest was in SL_1. These conditions triggered drought in some locations. The highest drought index occurred in August (56,89%), while the lowest occurred in July (3.98%). Based on hidroclimatological ,the prioritised locations for escalated productivity are paddy fields in CDK.16 Ka, CDK.17 Ki, PD.1 Ka, PD.1 Ki, PD.2 Ka, PD.2 Ki, CRJ.6 Ki, CRJ.7 Ki, CRJ.8 Ki, CRJ.9 Ki, CRJ.10 Ki, and CKR.1 Ki in the Ciranjang subdistrict. Meanwhile, to gain the equal irrigation distribution, the priority locations consist of paddy fields in CSK.1 Ki to CSK.5 ki, CSK.6 Ki, CSK.6 Ka, CSK.7 Ki to CSK.9 Ki, CSK.10 Ki, and CSK.10 Ka, situated in Bocongpicung District. Keywords: drought index, irrigation priority, water balance